(untitled) (Journal of Mining and Metallurgy, Section B: Metallurgy, 2013)
The aim of this work was to determine TTT diagram of medium carbon V-N micro-alloyed steel with emphasis on the development of intragranular ferrite morphologies. The isothermal treatment was carried out at 350, 400, 450, 500, 550 and 600 οC. These treatments were interrupted at different times in order to analyze the evolution of the microstructure. Metallographic evaluation was done using optical and scanning electron microscopy (SEM). The results show that at high temperatures (≥ 500 ○C) polygonal intragranulary nucleated ferrite idiomorphs, combined with grain boundary ferrite and pearlite were produced and followed by an incomplete transformation phenomenon. At intermediate temperatures (450, 500 ○C) an interloced acicular ferrite (AF) microstructure is produced, and at low temperatures (400, 350 ○C) the sheave of parallel acicular ferrite plates, similar to bainitic sheaves but intragranularly nucleated were observed. In addition to sheaf type acicular ferrite, the grain boundary nucleated bainitic sheaves are observed